Transesterification Of Glycerol With Dimethyl Carbonate To Glycerol Carbonate Over Ash-, Clay- Based And Strontium-Aluminum Mixed Oxide Catalysts - Algoufi, Yoseef Turky (2013)
The global growth in biodiesel production over the past decade has led to the availability of significant quantities of glycerol as a by-product of the triglyceride transesterification process. Glycerol (GL) is a versatile feedstock for producing chemicals such as glycerol carbonate (GC) which can be produced by the transesterification of glycerol with dimethyl carbonate (DMC) over base catalyst. In this work, dolomite, sodium rich clay, oil palm ash and K-zeolite synthesized form fly ash have been utilized as low-cost heterogeneous basic catalysts for GC synthesis from GL and DMC. The study was conducted in a batch reactor at different reaction conditions (1-7 wt%) catalyst loading; (1:1-4:1) DMC:GL molar ratio; (55-75 OC) reaction temperature and (0.5-2 h) reaction time. At the best operating conditions of 5 wt% catalyst loading; 3:1 DMC: GL molar ratio; 75 OC reaction temperature and 1.5 h reaction time, the yields of GC obtained were 98.4%, 97.3%, 96.4% and 94% for Na-clay, oil palm ash, K-zeolite and dolomite, respectively. In terms of catalyst reusability and leaching, all catalysts suffered from leaching of metallic species in range between (4.23-31%) and the best catalytic performance was obtained by Na-clay where the minimum leaching was occurred (4.23%) compared to other low-cost catalysts and it was used successfully for four cycle runs. Strontium-aluminum mixed oxide catalyst was also developed in order to have more stable and unleachable heterogeneous catalyst for GC synthesis from GL and DMC.